2021
DOI: 10.3390/medsci10010003
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide: The Missing Factor in COVID-19 Severity?

Abstract: Coronavirus disease 2019 (COVID-19) is a contagious respiratory and vascular disease that continues to spread among people around the world, mutating into new strains with increased transmission rates, such as the delta variant. The scientific community is struggling to discover the link between negative COVID-19 outcomes in patients with preexisting conditions, as well as identify the cause of the negative clinical patient outcomes (patients who need medical attention, including hospitalization) in what seems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 91 publications
0
10
0
3
Order By: Relevance
“…An inducible NO synthase (NOS2, ENSG00000007171) was downregulated at the transcript level (–2.5 log-fold change; p = 3.36 × 10 −6 ). NOS2 generates NO, a messenger molecule with diverse functions in multiple human tissues [ 43 , 44 , 45 ]. Transcription of the arginine synthase ARG2 was also downregulated ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…An inducible NO synthase (NOS2, ENSG00000007171) was downregulated at the transcript level (–2.5 log-fold change; p = 3.36 × 10 −6 ). NOS2 generates NO, a messenger molecule with diverse functions in multiple human tissues [ 43 , 44 , 45 ]. Transcription of the arginine synthase ARG2 was also downregulated ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Gould et al [ 135 ] found that NO production was associated with oxidative stress caused by many types of viral infections. However, Nikolaidis et al [ 136 ] concluded that the comorbidities associated with negative clinical patient outcomes of COVID-19 sickness are linked to depletion of NO in the body.…”
Section: Identification Of Covid-19-specific Chemical Biomarkersmentioning
confidence: 99%
“…The increased severity of COVID-19 symptoms associated with old age and the age-related decline of NO levels have tied low NO levels to all major high-risk groups of COVID-19 infection. This correlation of low NO levels to increased COVID-19 infection severity and COVID-exclusive symptomatology, along with successful utilization of NO gas as a therapeutic option, should stimulate further research on this basis to further improve COVID-19 treatment options [ 136 ].…”
Section: Identification Of Covid-19-specific Chemical Biomarkersmentioning
confidence: 99%
“…Although multiple clinical trials for iNO are currently underway for use in COVID-19 ( Table 2 ), questions remain about dosage, frequency, and duration of administration - whether low dose continuous inhalation or short bursts of high dose NO like that in cigarettes [ 197 ]. Additionally, the requirement for skilled technicians, attributed financial costs, and possible adverse effects, including methemoglobinemia [ 282 ], etc., have been cited as potential obstacles to the clinical use of iNO. However, developing alternatives such as NONS, still requiring Phase 3 investigation, may reduce some of these challenges.…”
Section: No Delivery Platformsmentioning
confidence: 99%